2010
DOI: 10.1177/0042098010372683
|View full text |Cite
|
Sign up to set email alerts
|

World Cities of Scientific Knowledge: Systems, Networks and Potential Dynamics. An Analysis Based on Bibliometric Indicators

Abstract: This paper is based on identification of the pattern of the upper level of the world city network of knowledge as published in a series of earlier papers. It is our aim to update the findings and relate to the general world city discussion. The structure of the world cities of knowledge network has changed over the past decade in favour of south-east Asian and south European cities and in disfavour of the traditional centres of North America and north-western Europe. The analysis is based on bibliometric data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 30 publications
1
85
0
5
Order By: Relevance
“…Como exemplo, a cidade de São Paulo concentra cerca de 20% da produção científica brasileira e cresceu 21 posições na lista das cidades de maior geração de conhecimento no mundo durante a última década. Por conta disso, passou a figurar dentre os 20 municípios que mais produziram ciência no mundo (Royal Society, 2011), destacando-se internacionalmente entre as cidades que mais apresentaram crescimento na produção científica recentemente (Matthiessen et al, 2010). No caso brasileiro, a concentração espacial está diretamente relacionada à localização dos campi das universidades públicas, primordialmente as estaduais e federais, uma vez que essas são responsáveis pela maioria da atividade científica, padrão típico de países em desenvolvimento.…”
Section: A Geografia Da Ciência E Da Colaboraçãounclassified
“…Como exemplo, a cidade de São Paulo concentra cerca de 20% da produção científica brasileira e cresceu 21 posições na lista das cidades de maior geração de conhecimento no mundo durante a última década. Por conta disso, passou a figurar dentre os 20 municípios que mais produziram ciência no mundo (Royal Society, 2011), destacando-se internacionalmente entre as cidades que mais apresentaram crescimento na produção científica recentemente (Matthiessen et al, 2010). No caso brasileiro, a concentração espacial está diretamente relacionada à localização dos campi das universidades públicas, primordialmente as estaduais e federais, uma vez que essas são responsáveis pela maioria da atividade científica, padrão típico de países em desenvolvimento.…”
Section: A Geografia Da Ciência E Da Colaboraçãounclassified
“…It has been known for a long time that cities are at the forefront of the development of science and technology with most research activities concentrated around major metropolitan areas and that the top 75 science-producing clusters in the world from 2006 to 2008 generated some 57% of the research and publishing 3.9 million papers (Matthiessen et al, 2010). Work based on data on patents (Youn et al, 2014) noted that with 97% of inventions between 2000 and 2010 having been made in urban areas.…”
Section: Copyright©world Technopolis Associationmentioning
confidence: 99%
“…What is of interest is how to identify the factors that drive successful research clusters which can then help city planners and policy-makers decide on what kind of investment is needed to make cities work in this way and more importantly what measures are valid in trying to analyse these factors (Matthiessen et al, 2010;Van Noorden, 2010) to try inform those building profitable centres to drive employment creation. An analysis by Strumsky (2014) has shown that size of the city has a very strong influence on productivity in terms of invention and innovation.…”
Section: Copyright©world Technopolis Associationmentioning
confidence: 99%
“…No entanto, grande parte dos trabalhos utilizam variáveis que podem ser consideradas proxyda capacidade das centralidades de gerar e absorver fluxos materiais e imateriais, a exemplo das avaliações sobre a atuação das organizações coorporativas globais ou da infraestrutura diretamente ligada ao nível de conectividade das centralidades, embora isso não forneça elementos convincentes sobre a direção e o sentido desses fluxos. Derudderet al(2010Derudderet al( ,p.1862 Estudos recentes têm buscado explorar o poder de centralidade das cidades com base em várias estratégias metodológicas, a exemplo de trabalhos que exploram dados sobre infraestrutura de internet (VINCIGUERRA et al, 2010), tráfego aéreo (SMITH;TIMBERLAKE, 1995, MAHUTGA et al, 2010, escritórios de empresas de serviços avançados (DERUDDER et al, 2003;TAYLOR, 2004;DERUDDER et al, 2010), as relações dentro de empresas transnacionais (ALDERSON; BECKFIELD, 2004) e até mesmo sobre volume de publicações científicas (MATTHIESSEN et al, 2010). Diante dessa diversidade de olhares, a centralidade das cidades depende, em certa medida, de que tipo de laço interurbano está sendo considerado (CARROLL, 2007).…”
Section: As Principais Cidades Do Mundo E As Recentes Abordagens Empíunclassified